Sistem Pelayanan Jasa Tour and Travel Berbasis Web - Gilang Eko Prasetyo; Dyah Ayu Megawaty; Ade Dwi Putra (Jurnal Ilmiah Informatika dan Ilmu Komputer (JIMA-ILKOM), 2023)
The purpose of this research is to develop a web-based tour and travel service system for the JC Tour and Travel company. The development method used is Extreme Programming. The development of this system involves the use of several tools such as XAMPP, Visual Studio Code, and Mozilla Firefox. The programming languages used are PHP, HTML, and CSS, with MySQL as the database. Testing was carried out using the Black Box Testing method. This system aims to provide efficient and easy-to-use solutions for customers in planning and ordering travel services, as well as assisting companies in managing and managing their operations. Some of the features developed in this system include searching for destinations and packages, ordering and paying online, and updating order status in real-time. It is hoped that the results of this research can provide a better experience for customers by implementing an effective Extreme Programming method and proper testing.